2009
DOI: 10.1073/pnas.0907039106
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory recruitment of signaling proteins to cell tips promotes coordinated behavior during cell fusion

Abstract: Cell-cell communication is essential for coordinating physiological responses in multicellular organisms and is required for various developmental processes, including cell migration, differentiation, and fusion. To facilitate communication, functional differences are usually required between interacting cells, which can be established either genetically or developmentally. However, genetically identical cells in the same developmental state are also capable of communicating, but must avoid self-stimulation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
235
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(250 citation statements)
references
References 39 publications
8
235
1
2
Order By: Relevance
“…However, its expression was up-regulated more strongly in the incompatible interaction. This is consistent with the fact that the MAPK pathway is known to regulate related processes such as hyphal fusion and autophagy (Codogno and Meijer, 2005;Lam et al, 2006;Thaiville et al, 2008;Fleissner et al, 2009;Gough, 2010).…”
Section: Discussionsupporting
confidence: 67%
“…However, its expression was up-regulated more strongly in the incompatible interaction. This is consistent with the fact that the MAPK pathway is known to regulate related processes such as hyphal fusion and autophagy (Codogno and Meijer, 2005;Lam et al, 2006;Thaiville et al, 2008;Fleissner et al, 2009;Gough, 2010).…”
Section: Discussionsupporting
confidence: 67%
“…Remarkably, another essential protein for CAT fusion, with unknown function, soft (SO) [17], exhibited a complementary oscillatory pattern, with a maximum intensity in one cell synchronized with the maximum of MAK-2 in the other. Fleißner et al [20] suggested that the MAK-2 peaks correspond to the receiving of a signal while the SO maxima to the sending of it (see Fig. 1C).…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of the gene encoding the MAP kinase MAK-2 resulted in cells unable to chemotropically home and fuse with other, even normal, wild-type, cells. To shed light on the cellular localization of this kinase, Fleißner et al [20] genetically tagged MAK-2 with green fluorescent protein (GFP). Unexpectedly, they found that in the CATs undergoing chemotropic homing, MAK-2 localized to the plasma membrane at the CAT tips periodically in time, reaching maximum intensity every 10-12 min (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, each of the two cells not only stimulates directed growth of the partner, but also avoids self-stimulation by the signal [57]. It is conceivable that similar systems could be used for cell-cell recognition during organogenesis in multicellular organisms.…”
Section: Finding the Right Partner: Cell-cell Recognition Self-avoidmentioning
confidence: 99%
“…However, a chemokine signalling mechanism must avoid self-stimulation and therefore cannot readily explain mutual attraction, unless the two partner cells use different chemokines and complementary receptors. A fascinating solution to this problem was described in vegetative hyphal fusion in the Ascomycete Neurospora crassa [57]. Here, genetically identical cells, as in case of tracheal FCs, are able to sense each other in close proximity by communicating via chemoattractants.…”
Section: Finding the Right Partner: Cell-cell Recognition Self-avoidmentioning
confidence: 99%